Kierunek zmian w otoczeniu regulacyjnym polskiego rynku kapitałowego dla emitentów papierów wartościowych w latach 1991-2005 - Majerowicz, Justyna (Major changes on the Polish capital market for issuers of securities in 1991-2005, 2006)
This article indicates the most important changes for issuers introduced on Polish capital market in 1991-2005. The author describes changes which were made by the amendment to the Law on the public trading of securities and investment funds dated 22nd march 1991 and to the Law on the public trading of securities dated 21st august 1997, and changes which have been introduced by three acts passed by the Parliament on July 29th 2005 which are now a new constitution of the Polish capital market. The new law came into force on October 24th 2005. The changes aim mainly at increasing the role of the Polish capital market in the economy. These three acts are: 1. On public offering, conditions governing an introduction of financial instruments to organised trading and public companies („act on offering and companies”). 2. On trading in financial instruments (“act on trading”). 3. On capital market supervision (“act on supervision”). Changes are based on three basic assumptions: 1) stimulation of competition and liberalization for issuers (allowing trading off the regulated market, wider forms of trading); 2) full harmonisation with EU regulations (implementation of prospectus directive); 3) three acts regulating the whole capital market (primary market, secondary market and supervision are regulated separately, breakout complies better with EU rules on law-making and will facilitate further harmonisation with new EU regulations).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 304-312